Participatory varietal selection in rapeseed-mustard (Journal of Oilseed Brassica, 2026)
The present investigation of PVS in rapeseed-mustard comprised of nine mother trials were successfully conducted across four predominant oilseed districts of Kashmir valley during 2013-14 and 2014-15. In addition to it, twenty four baby trials (12 each year) of Shalimar sarson-1 and Shalimar sarson-2 each of 500m2 area along with farmer’s variety as check were conducted across the villages and over the years. All the trials were managed by the farmers under the supervision of breeder. The farmer walk was organized by the researchers at the farmer’s field prior to harvest of the crop and farmers were allowed to select the varieties in a secret ballot box. On the basis of overall ranking of varieties by the farmers, the Shalimar sarson-1 & Shalimar sarson-2 (not notified) were the selected by the farmers across most of the districts. The main aim of the study was to increase the adoption of modern varieties to suit their agroecological nichesof the valley.